Pengaruh Pendidikan Kesehatan Seksual terhadap Pengetahuan dan Sikap Remaja dalam Upaya Pencegahan Penularan HIV/AIDS di Kodia Yogyakarta - Chairul Fuad, Sunardi Radiono, Ira Paramastri (Berita Kedokteran Masyarakat (BKM), 2003)
Background: The adolescent's sexual activity tends to be unplanned and unprotected which might results in negative impact such as illegal pregnancy, STD and HIVIAIDS. The high risk of adolescent's STD and HIV/AIDS is the impact of their sexual behaviour and their lack of information or never obtain education and service about sexual and reproduction health. In relationship with this matter, adolescents need to be given sexual health education with an expectation that they wilt not perform unhealthy sexual rela-tionship. PKBI DIY has conducted this activity for high school students through Peer Education in Yogyakarta.Aim: This research was aimed to find out the influence of sexual health education toward knowledge and attitude of teenager in the prevention of HIV/AIDS transmission. It was conducted toward students who obtained sexual health education through Peer Education (as Peer Education) in 11 high schools in Yogyakarta. It was a quasi-experi-mental research with posttest only control group design that seeks for the influence of independent variable that was sexual health education toward dependent variable (knowl-edge and attitude of teenager in the prevention of HIV/AIDS transmission) and qualita-tive study in order to find out the benefit and effectiveness from sexual health educa-tion. Method: Data were gathered with structured questioner and Focus Group Discussion (FGD).Result: The result of t-test showed that sexual health education had significant influ-ence toward the improvement of adolescent's knowledge (p=0,000 or < 0,05) and did not have significant influence toward the attitude of teenager (p=0,165 or > 0,05). Conclusion: Qualitative data that was obtained from FGD showed that Peer Education still not yet optimum, and there is a need of improvement on accurate and actual mate-rials, facilitators quality, education media, school's cooperation, communication tech-nique skill of Peer Educator and Peer Educator activity. Therefore, Peer Education ap-proach could be used as one alternative approach for prevention of HIV/AIDS transmis-sion. Keywords: sexual health education, Peer Education, HIV/AIDS